Embryonic temperature and the genes regulating myogenesis in teleosts - Macqueen, Daniel J. (University of St Andrews, 2008)
In this study, full coding sequences of Atlantic salmon (Salmo salar L.) muscle genes were cloned, including myogenic regulatory factors (MRFs) (myod1c, myog, mrf4, myf5), inhibitors of Myostatin (fst, decorin), markers of myogenic progenitor cell (MPC) proliferation (sox8) and fusion (calpastatin), a marker of slow muscle fibre differentiation (smlc1) and a novel eukaryotic gene involved in regulating growth (cee). Several of these genes were then characterised using a range of experimental and computational analyses with the aim to better understand their role in myogenesis and their evolution in teleosts. A series of experiments supported previous findings that teleosts have extra copies of many genes relative to tetrapods as a result of a whole genome duplication (WGD) event that occurred some 320-350 Mya. For example, it was shown that genes for myod and fst have duplicated in a common teleost ancestor, but were then specifically lost or retained in different lineages. Furthermore, several characterised Atlantic salmon genes were conserved as paralogues, likely from a later WGD event specific to the salmonid lineage. Phylogenetic reconstruction and comparative genomic approaches were used to characterise the evolution of teleost paralogues within a framework of vertebrate evolution. As a consequence of one experiment, a revised nomenclature for myod genes was proposed that is relevant to all diploid and polyploid vertebrates. The expression patterns of multiple myogenic genes were also established in Atlantic salmon embryos using specific complementary RNA probes and in situ hybridization. For example, co-ordinated embryonic expression patterns were revealed for six salmon MRFs (myod1a, myod1b, myod1c, myog, mrf4, myf5), as well as markers of distinct MPC populations (pax7, smlc1), providing insight into the regulatory networks governing myogenesis in a tetraploid teleost. Furthermore, it was shown that Atlantic salmon fst1 was expressed concurrently to pax7 in a recently characterised MPC population ...